Anak Indonesia Pencipta AI untuk Pendidikan - Melvinda Dewi Kirana; Masduki Asbari; Risma Rusdita (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to determine technological developments, namely artificial intelligence or often called AI (Artificial Intelligence). In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from Helmy Yahya Talk's YouTube channel entitled "Indonesian Children Create AI for Education" which he explained. The results of this study explain that through artificial intelligence, MASA AI is determined to provide the best educational solutions for 150 million Indonesian workers and 50 million students. With the support of resources from Silicon Valley, MASA AI believes that access to quality education is a right for everyone. Continuous advances in information technology, such as artificial intelligence (AI), open up new and exciting opportunities for shared value creation among economic actors.